Oxygen isotope anomaly in tropospheric CO2 and implications for CO2 residence time in the atmosphere and gross primary productivity. Issue 1 (December 2017) - Liang, Mao-Chang; Mahata, Sasadhar; Laskar, Amzad; Thiemens, Mark; Newman, Sally
Abstract The abundance variations of near surface atmospheric CO2 isotopologues (primarily16 O12 C16 O, 16 O13 C16 O, 17 O12 C16 O, and18 O12 C16 O) represent an integrated signal from anthropogenic/biogeochemical processes, including fossil fuel burning, biospheric photosynthesis and respiration, hydrospheric isotope exchange with water, and stratospheric photochemistry. Oxygen isotopes, in particular, are affected by the carbon and water cycles. Being a useful tracer that directly probes governing processes in CO2 biogeochemical cycles, Δ17 O (=ln(1 + δ17 O) − 0.516 × ln(1 + δ18 O)) provides an alternative constraint on the strengths of the associated cycles involving CO2 . Here, we analyze Δ17 O data from four places (Taipei, Taiwan; South China Sea; La Jolla, United States; Jerusalem, Israel) in the northern hemisphere (with a total of 455 measurements) and find a rather narrow range (0.326 ± 0.005‰). A conservative estimate places a lower limit of 345 ± 70 PgC year−1 on the cycling flux between the terrestrial biosphere and atmosphere and infers a residence time of CO2 of 1.9 ± 0.3 years (upper limit) in the atmosphere. A Monte Carlo simulation that takes various plant uptake scenarios into account yields a terrestrial gross primary productivity of 120 ± 30 PgC year−1 and soil invasion of 110 ± 30 PgC year−1, providing a quantitative assessment utilizing the oxygen isotope anomaly for quantifying CO2 cycling.